Patient Variables Associated with Nafcillin Plasma Concentrations and Toxicity. Issue 9 (1st September 2016) - Benefield, Russell J.; Barker, Brian C.; Gast, Christopher M.; Alexander, Donald P.
Abstract : Objectives: Primary objective: To retrospectively review nafcillin plasma concentrations (CNAF ) and determine nafcillin clearance (CLNAF ) in a diverse sample of patients treated with nafcillin administered as a continuous infusion. Secondary objective: To identify clinical variables associated with CLNAF and nafcillin‐related adverse drug reactions (ADRs). Methods: Retrospective chart review of patients receiving nafcillin via continuous infusion at University of Utah Health Care from 2006 to 2013 who had at least one steady‐state CNAF measured. CLNAF was determined by dividing the nafcillin rate of infusion by CNAF . Adverse drug reactions (ADRs) were defined using the National Institutes of Health, Division of Microbiology and Infectious Diseases criteria and scored for probability of association with nafcillin by using Naranjo criteria. Multivariate models were constructed to identify independent variables associated with CLNAF and ADRs. Main results: Seventy‐six CNAF from 54 patients were included. Median CLNAF was 13.9 L/hour (range ≤ 4.2 to 36.9 L/hr). Congestive heart failure (p=0.007), hyperbilirubinemia (p<0.0001), and serum creatinine (p<0.0001) were associated with reduced CLNAF, and Hispanic race (p=0.002) was associated with increased CLNAF by multivariate analysis. Twenty patients (37.0%) experienced an ADR. CNAF were significantly higher between patients that experienced an ADR and those that did not (66.0 vs 25.5 mg/L, p<0.001). Individual ADRs associated with CNAF included hepatotoxicity (62.8 vs 27.0 mg/L, p=0.001), nausea/vomiting (80.0 vs 28.5 mg/L, p=0.01), and diarrhea (66.5 vs 26.5 mg/L, p<0.001). Multivariate analysis identified CNAF as being independently associated with ADRs. A putative toxicity relationship between CNAF and predicted probability of ADR was established. Conclusions: Several patient variables were associated with impaired CLNAF, and elevated CNAF were associated with ADRs. Additional studies assessing the utility of nafcillin therapeutic drug monitoring to minimize toxicity are warranted.